Paneth Cell Ablation Aggravates Pancreatic and Intestinal Injuries in a Rat Model of Acute Necrotizing Pancreatitis after Normal and High-Fat Diet - Yuecheng Guo; Chunlan Huang; Liyan Liu; Xinyuan Fu; Yingying Lu; Junyuan Zheng; Qixiang Mei; Zehua Huang; Junjie Fan; Lungen Lu; Yue Zeng (Hindawi Limited, 2019)
We previously reported that acute necrotizing pancreatitis (ANP) after normal or high-fat diet is associated with a decreased number of Paneth cells in ileal crypts. Here, we ablated Paneth cells in a rat model of ANP after normal and high-fat diet to investigate the effects on disease symptoms. Adult male Sprague-Dawley rats received standard rat chow or a high-fat diet for 2 weeks, after which they were treated with dithizone to deplete Paneth cells. Six hours later, ANP was established by retrograde injection of sodium taurocholate into the biliopancreatic duct. Rats were sacrificed at 6, 12, and 24 h for assessment. We found dithizone aggravated ANP-associated pathological injuries to the pancreas and ileum in rats on high-fat or standard diets. Lysozyme expression in ileal crypts was decreased, while serum inflammatory cytokines (TNFα, IL-1β, and IL-17A) and intestinal permeability (serum DAO activity and D-lactate) were increased. Expression of tight junction proteins (claudin-1, zo-1, and occludin) was decreased. Using high-throughput 16S rRNA sequencing, we found dithizone reduced microbiota diversity and altered microbiota composition in rats on high-fat or standard diets. Dithizone decreased fecal short-chain fatty acids (SCFAs) in rats on high-fat or standard diets. Changes in intestinal microbiota correlated significantly with SCFAs, lysozyme, DAO activity, D-lactate, inflammatory cytokines, and pathological injury to the pancreas and ileum in rats on high-fat or standard diets. In conclusion, ablation of Paneth cells exacerbates pancreatic and intestinal injuries in ANP after normal and high-fat diet. These symptoms may be related to changes in the intestinal microbiota.